Goldfish On Vacation - Lloyd-Jones, Sally, 1960-; Espinosa, Leo (New York : Schwartz & Wade Books, 2018)
Three goldfish live in a small bowl, in an apartment building, in the middle of a big city, until one summer they get to go on vacation--in a fountain, with lily pads, and reeds, and other neighborhood goldfish.
new kids book 2023 fall.
Ages 4-8.
Keywords: Goldfish -- Juvenile fiction; Vacations -- Juvenile fiction; Fountains -- Juvenile fiction; Goldfish -- Fiction; Fountains -- Fiction; Fishes -- Fiction; Vacations -- Fiction